Operations order (CDRU [S.l.], 2001)
Represents the response of the military and police elements of the Regional Security System to a national disaster. Reflects the mandate of the Caribbean Disaster Emergency Response Agency (CDERA) and the relationship between the two organisations.
Keywords: DISASTER MANAGEMENT